Studying the effects of locally used methods of preparing unripe grape juice on its total phenolic content and its antioxidant activity - محمد, مرح; زينب صارم (Latakia University Journal -Medical Sciences Series, 2024)
Vegetables, fruits and their products are considered as protective foods against cardiovascular diseases (CVDs). They may reduce metabolic disorders which increase the incidence of these diet - related diseases. They contain many bioactive components like phenolic compounds, which are natural antioxidants. In this study, in Syria highly consumed unripe grape juice was selected as a phenolic compounds- rich food. This research aims to study the effect of the preparing method of unripe grape juice on its levels of phenolic compounds and its antioxidant activity. Fresh unripe grape juice (Vitis vinifera L.) was prepared and heat-treated either by exposing it to sunlight for 30 days (unboiled unripe grape juice) or boiling it for 60 minutes (boiled unripe grape juice). Then the resulting juice was stored at room temperature for a year. Total phenolic content in the unripe grape juice prepared by previously mentioned methods was determined using Folin-Ciocalteau method, and the antioxidant activity of this juice was compared using the Reducing Power method. Additionally, the total phenolic content and the antioxidant activity of the for one year stored juice were measured and compared at three-month intervals. The results showed a positive correlation between the total phenolic content of unripe grape juice (either boiled or unboiled) and its antioxidant activity. However, the newly prepared boiled unripe grape juice showed the highest content of phenolic compounds and the highest reducing power than unboiled unripe grape juice. Despite the statistically significant decrease in both total phenolic content and antioxidant activity of one year stored unripe grape juice prepared by boiling or not, boiled juice showed the highest phenolic content and the highest antioxidant activity than unboiled juice.